2004
DOI: 10.1080/10236210490474458
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Effectiveness and Heat Transfer Coefficient of Shaped Film Cooling Holes on a Scaled Guide Vane Pressure Side Model

Abstract: The demand of improved thermal efficiency and high power output of modern gas turbine engines leads to extremely high turbine inlet temperature and pressure ratios. Sophisticated cooling schemes including film cooling are widely used to protect the vanes and blades of the first stages from failure and to achieve high component lifetimes. In film cooling applications, injection from discrete holes is commonly used to generate a coolant film on the blade's surface. In the present experimental study, the film coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…10 and 11. According to the analysis in previous studies [15,19] which the authors agree with, this ''fork tines'' pattern of enhanced heat transfer is caused by the counter-rotating vortex pair shown in Fig. 8 which could thicken the boundary layer in the centerline region of film jet and thin the boundary layer at the lateral edges of the film jet.…”
Section: Heat Transfer Coefficientmentioning
confidence: 65%
See 2 more Smart Citations
“…10 and 11. According to the analysis in previous studies [15,19] which the authors agree with, this ''fork tines'' pattern of enhanced heat transfer is caused by the counter-rotating vortex pair shown in Fig. 8 which could thicken the boundary layer in the centerline region of film jet and thin the boundary layer at the lateral edges of the film jet.…”
Section: Heat Transfer Coefficientmentioning
confidence: 65%
“…[11][12][13][14][15][16]. Guo et al [11] found that fanshape holes produced higher cooling effectiveness and lower heat transfer coefficient than cylindrical holes on both suction and pressure side of a nozzle vane model in a transonic annular cascade.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, they reported that further increase in the blowing ratio results in a reverse effect. Dittmar et al [8] measured adiabatic film cooling effectiveness and the heat transfer coefficient of single row of fan shaped holes and a double row of cylindrical holes in staggered arrangement. During their measurements, the influence of blowing ratio and mainstream turbulence level on the adiabatic film cooling effectiveness and heat transfer coefficient is investigated for both of the injection configurations.…”
Section: Introductionmentioning
confidence: 99%